Experimental research of the synthetic jet generator designs based on actuation of diaphragm with piezoelectric actuator. (January 2015) - Rimasauskiene, R.; Matejka, M.; Ostachowicz, W.; Kurowski, M.; Malinowski, P.; Wandowski, T.; Rimasauskas, M.
Abstract: Experimental analyses of four own developed synthetic jet generator designs were presented in this paper. The main task of this work was to find the most appropriate design of the synthetic jet generator. Dynamic characteristics of the synthetic jet generator׳s diaphragm with piezoelectric material were measured using non-contact measuring equipment laser vibrometer Polytec ® PSV 400. Temperatures of the piezoelectric diaphragms working in resonance frequency were measured with Fiber Bragg Grating (FBG) sensor. Experimental analysis of the synthetic jet generator amplitude–frequency characteristics were performed using CTA (hot wire anemometer) measuring techniques. Piezoelectric diaphragm in diameter of 27 mm was excited by sinusoidal voltage signal and it was fixed tightly inside the chamber of the synthetic jet generator. The number of the synthetic jet generator orifices (1 or 3) and volume of cavity (height of cavity vary from 0.5 mm to 1.5 mm) were changed. The highest value of the synthetic jet velocity 25 m/s was obtained with synthetic jet generator which has cavity 0.5 mm and 1 orifice (resonance frequency of the piezoelectric diaphragm 2.8 kHz). It can be concluded that this type of the design is preferred in order to get the peak velocity of the synthetic jet. Graphical abstract: Highlights: Experimental analyses of four developed synthetic jet generator designs were presented in this paper. Dynamic characteristics of the diaphragm with piezoelectric material were measured. Experimental analysis of the synthetic jet generator amplitude–frequency characteristics was performed.